Shock Wave-Activated Silver-Loaded Biopolymer Implant Coating Eliminates Staphylococcus epidermidis on the Surface and in the Surrounding of Implants - Martin Schulze; Melanie Nonhoff; Julian Hasselmann; Manfred Fobker; Silke Niemann; Christoph Theil; Georg Gosheger; Jan Puetzler (MDPI AG, 2023)
Bacterial biofilms on foreign surfaces are considered a primary cause of implant-related infections, which are challenging to treat. A new implant coating was developed, containing anti-infective silver within a biocompatible polymer carrier substance. In addition to its passive effect on the implant surface, highly concentrated anti-infective silver can be released as needed via the application of high-energy shock waves. This intervention could be applied transcutaneously in a clinical setting without the need for additional surgery. We investigated the inhibition of biofilm formation and the effectiveness of eradication after activation of the coating via shock waves in an in vitro biofilm model using Staphylococcus epidermidis RP62A. This was performed via scanning electron microscopy and quantitative microbiology. Additionally, we examined the cytotoxicity of the new coating on normal human fibroblasts and Saos-2 osteoblast-like cells, depending on the silver concentration. All studies were compared to uncoated titanium surfaces Ti6Al4V and a conventional electroplated silver coating. Cytotoxicity toward normal human fibroblasts and Saos-2 osteoblast-like cells increased with higher silver content but remained tolerable at 6%. Compared to uncoated Ti6Al4V and the electroplated silver coating, the new coating with a silver content of 4% and 6% exhibited a significant reduction in adherent bacteria by a factor of approximately 1000. This was also evident via microscopic examination of the surface morphology of the biofilms. Furthermore, following shock wave activation, no bacteria were detectable on either the implant or in the surrounding fluid after a 24 h period.